Leadership in Action : Getting a Grip on Conflict - Sharpe, Davida (Center for Creative Leadership, 2001)
The ability to manage conflict plays a key role in determining whether an executive will continue on a successful career path or will derail. Recognizing and resolving conflict can be difficult, however. Here's a step-by-step guide that will help executives master this important skill.